2015
DOI: 10.1098/rspb.2014.1850
|View full text |Cite
|
Sign up to set email alerts
|

Does early learning drive ecological divergence during speciation processes in parasitoid wasps?

Abstract: Central to the concept of ecological speciation is the evolution of ecotypes, i.e. groups of individuals occupying different ecological niches. However, the mechanisms behind the first step of separation, the switch of individuals into new niches, are unclear. One long-standing hypothesis, which was proposed for insects but never tested, is that early learning causes new ecological preferences, leading to a switch into a new niche within one generation. Here, we show that a host switch occurred within a parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 64 publications
4
72
0
Order By: Relevance
“…After the appointment of Steidle as the head of the Department of Animal Ecology at Hohenheim University, Germany, another center of L. distinguendus research was established. Steidle focused on basic research about the mechanisms of speciation with a focus on early learning and courtship behavior, using L. distinguendus as a model system [66]. It could be shown that the species L. distinguendus de facto consists of two species.…”
Section: From the Late 1990s–presentmentioning
confidence: 99%
See 3 more Smart Citations
“…After the appointment of Steidle as the head of the Department of Animal Ecology at Hohenheim University, Germany, another center of L. distinguendus research was established. Steidle focused on basic research about the mechanisms of speciation with a focus on early learning and courtship behavior, using L. distinguendus as a model system [66]. It could be shown that the species L. distinguendus de facto consists of two species.…”
Section: From the Late 1990s–presentmentioning
confidence: 99%
“…It could be shown that the species L. distinguendus de facto consists of two species. While one of these two species is a generalist on many different hosts, the other apparently has a narrower host range and is unwilling to parasitize S. granarius , a fact that could have a huge impact on the application [66]. Furthermore, Steidle picked up earlier applied work looking at the dispersal ability of L. distinguendus , this time studying the dispersal of the wasps outside the commodity, applied as an empty storage treatment against residual pest populations [67].…”
Section: From the Late 1990s–presentmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, knowledge of phylogenetic relatedness can be used to predict the host range of a biological control agent or target pest (Sheppard et al, 2005). However, predicting potential host ranges should not be based solely on phylogenetic relationships because numerous ecological (Hoffmeister, 1992;Stireman and Singer, 2003) and behavioral (König et al, 2015) factors also influence host associations. When explicit phylogenies are unavailable, biological classifications can be harnessed to select sets of species appropriate for testing.…”
Section: Using Phylogenies and Classifications To Predict Host Rangesmentioning
confidence: 99%